2018
DOI: 10.1111/pai.12888
|View full text |Cite
|
Sign up to set email alerts
|

Early food allergy and respiratory allergy symptoms and attention‐deficit/hyperactivity disorder in Chinese children: A cross‐sectional study

Abstract: Early food allergy is associated with ADHD in school-age children. Early food allergy and respiratory allergy symptoms independently and synergistically contributed to higher risk of ADHD. Monitoring food allergy in early life could help in the early prediction and intervention for the consequent allergy march and ADHD in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Food intake may affect the behavior of children with ADHD through a mechanism that involves a non-IgE-mediated, cell-mediated or non-allergic response (167). A cross-sectional study from China suggested that early food allergies in school-age children are associated with ADHD (168). Children with ADHD reacted severely to allergenic foods including cow's milk, wheat and eggs (167,169).…”
Section: Inflammation/mcs and Adhdmentioning
confidence: 99%
“…Food intake may affect the behavior of children with ADHD through a mechanism that involves a non-IgE-mediated, cell-mediated or non-allergic response (167). A cross-sectional study from China suggested that early food allergies in school-age children are associated with ADHD (168). Children with ADHD reacted severely to allergenic foods including cow's milk, wheat and eggs (167,169).…”
Section: Inflammation/mcs and Adhdmentioning
confidence: 99%
“…19 Moreover, allergic reactions have been proposed to foster an imbalance in cholinergic/adrenergic activity within the central nervous system, leading to ADHD behaviours in some children, and were reported to independently and synergistically contribute to a higher risk of ADHD in children. 20 These potential confounders were all adjusted for in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is consistent evidence from populationbased studies of a significant association between asthma and attention deficit hyperactivity disorder (ADHD) both in children and adults 46,47 . Interestingly, also the allergic multimorbidity has been associated with higher ADHD 48 . Depression and anxiety, the most common mental health disorders, have also been associated with allergic diseases or their multimorbidity both in children and adults at the population level 43,49,50 .…”
Section: Beyond Medallmentioning
confidence: 99%